2020
DOI: 10.1128/mbio.01453-20
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Virus Ensures Viral Stability in the Hemolymph of Vector Insects through Suppressing Prophenoloxidase Activation

Abstract: Most plant viruses require vector insects for transmission. Viral stability in the hemolymph of vector insects is a prerequisite for successful transmission of persistent plant viruses. However, knowledge of whether the proteolytic activation of prophenoloxidase (PPO) affects the stability of persistent plant viruses remains elusive. Here, we explored the interplay between rice stripe virus (RSV) and the PPO cascade of the vector small brown planthopper. Phenoloxidase (PO) activity was suppressed by RSV by app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The insect hemolymph, which is critical in persistent viral transmissions by insect vectors, can be used as a bridge to the salivary glands (Liu et al, 2015;Chen X. et al, 2020). Besides, it is well-defended by the immune system, which can effectively remove microorganisms (such as bacteria, fungi, and viruses) (Lavine and Strand, 2002;Blow and Douglas, 2019).…”
Section: Bacterial Symbionts Contributing To the Stability Of Plant Viruses In Vector Hemolymphmentioning
confidence: 99%
See 1 more Smart Citation
“…The insect hemolymph, which is critical in persistent viral transmissions by insect vectors, can be used as a bridge to the salivary glands (Liu et al, 2015;Chen X. et al, 2020). Besides, it is well-defended by the immune system, which can effectively remove microorganisms (such as bacteria, fungi, and viruses) (Lavine and Strand, 2002;Blow and Douglas, 2019).…”
Section: Bacterial Symbionts Contributing To the Stability Of Plant Viruses In Vector Hemolymphmentioning
confidence: 99%
“…After viral particles are released from the midgut to the hemolymph, they can be recognized, targeted and cleared by the host immune system. Therefore, survival of virions within the hemolymph is vital for systemic dissemination of persistent viruses before entry into salivary glands (Liu et al, 2015;Chen X. et al, 2020). Van den Heuvel et al (1994) reported that chaperone proteins of endosymbionts may be involved in maintenance of plant viruses in the hemolymph.…”
Section: Bacterial Symbionts Contributing To the Stability Of Plant Viruses In Vector Hemolymphmentioning
confidence: 99%
“…Phenoloxidase is involved in the melanization pathway, one of the major innate immune responses of insects. RSV p3 binds cleavage sites of prephenoloxidase, preventing phenoloxidase activation by a cascade of clip-domain serine proteases and ensuring viral stability in the hemolymph [ 242 ].…”
Section: Transmissionmentioning
confidence: 99%
“…Additionally, the prophenoloxidase cascade is one of the major innate immune pathways that can restrict virus infection. Chen et al reported that RSV attenuates the prophenoloxidase response of the host to ensure virus stability in the hemolymph of vector insects [32] . Some animal viruses employ the mitogen-activated protein kinases of the host to establish successful infection.…”
Section: Insect Immunitymentioning
confidence: 99%